Topical analgesia for superficial corneal injuries. Issue 3 (May 1996) - Brahma, A K; Shah, S; Hillier, V F; McLeod, D; Sabala, T; Brown, A; Marsden, J
Abstract : OBJECTIVE–To assess the analgesic effects of a topical non-steroidal anti-inflammatory agent, flurbiprofen 0.03%, during healing after superficial corneal injuries. METHODS–401 patients treated for corneal abrasion in a five month period were randomly allocated to one of four treatment groups: polyvinyl alcohol alone (control), homatropine 2%, flurbiprofen 0.03%, or homatropine 2% followed by flurbiprofen 0.03%. Treatments were given for 48 h. Ocular pain was recorded on a visual analogue scale by the patients over the first 24 h, and use of oral analgesics was also recorded. Usable responses were received from 224 patients (55.8%). RESULTS–Patients treated with flurbiprofen had significantly lower pain scores for the 24 h duration of the study than controls (P < 0.05). CONCLUSIONS–Flurbiprofen eye drops provide more effective pain relief than traditional treatments for superficial corneal injuries.